Addressing Muslim transgenders' health issues using religious approach in the Malaysia setting - Suofeiya, Maliya; Razali, Zul Azlin; Mohd Subri, Irwan; Draman, Samsul; Md Isa, Muhammad Lokman; Ibrahim, Muhammad; Mokhtar, Rafidah Hanim (American Scientific Publishers, 2017)
Male-to-female transgenders are discriminated in Malaysia due to their gender expression, their involvement in the sex trade, and the high prevalence of HIV infection in this community. They are burdened by many health issues including HIV and sexually transmitted diseases, psychiatric problems, substance abuse, and complications resulting from feminizing procedures. Although majority of the transgender community is Muslim, many of them are far from religious guidance due to discrimination and fear towards criminalization. Efforts are needed to tackle the risks and vulnerability in health issues in the mak nyah community. This paper discusses the health issues faced by transgenders in Malaysia, and also describes an integrated method in helping the transgender community.